2022
DOI: 10.1021/acs.estlett.2c00159
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Aerosol Chemical Composition on Condensation Sink Efficiency and New Particle Formation in Beijing

Abstract: Relatively high concentrations of preexisting particles, acting as a condensation sink (CS) of gaseous precursors, have been thought to suppress the occurrence of new particle formation (NPF) in urban environments, yet NPF still occurs frequently. Here, we aim to understand the factors promoting and inhibiting NPF events in urban Beijing by combining one-year-long measurements of particle number size distributions and PM 2.5 chemical composition. Our results show that indeed the CS is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Lehtipalo et al (2016) have previously shown that if the concentrations of stabilizing vapors such as dimethylamine are high, resulting in low or negligible evaporation rates, cluster-cluster collisions can have a major contribution to the growth of clusters and particles, especially if CS is low. The same has also been observed in studies utilizing cluster population simulations (Kontkanen et al, 2022).…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…Lehtipalo et al (2016) have previously shown that if the concentrations of stabilizing vapors such as dimethylamine are high, resulting in low or negligible evaporation rates, cluster-cluster collisions can have a major contribution to the growth of clusters and particles, especially if CS is low. The same has also been observed in studies utilizing cluster population simulations (Kontkanen et al, 2022).…”
Section: Resultssupporting
confidence: 80%
“…However, it is possible that only a fraction of all the collisions lead to coagulation due to, e.g., chemical properties of the particles. This is analogous to the effectiveness of CS in removing condensable vapors such as sulfuric acid (Tuovinen et al, 2021(Tuovinen et al, , 2020, which has been shown to be higher for ammonium-nitrate-rich background particles (Du et al, 2022). If the effectiveness of CoagS for particles between 1.5 and 3 nm varies between 0.25 and 1.0, almost all of the observed J 3 /J 1.5 that are larger than predicted based on the simulations or L-2007 can be explained.…”
Section: Effect Of Uncertainties and Assumptions On Survival Probabil...mentioning
confidence: 74%
See 2 more Smart Citations
“…However, it is possible that only a fraction of all the collisions lead to coagulation due to e.g., chemical properties of the particles. This is analogous to effectiveness of CS in removing condensable vapors such as sulfuric acid (Tuovinen et al, 2021(Tuovinen et al, , 2020, which has been shown to be higher for ammonium-nitrate rich background particles (Du et al, 2022). If the effectiveness of CoagS for particles between 1.5 nm and 3 nm varies between 0.25 and 1.0, almost all the observed J3/J1.5 that are larger than predicted based on the simulations or L-2007 can be explained.…”
Section: Effect Of Uncertainties and Assumptions On Survival Probabil...mentioning
confidence: 67%